Spectral and Electrochemical Studies on Some Trinuclear Copper(II) and Dinuclear Cobalt(II) and Nickel(II) Macrocyclic Complexes - Rai, H.C. (Asian Journal of Chemistry, 2010)
Condensation of copper(II) complexes of the dialdehydes with bis (oxalodihydrazide) copper(II) complexes in aqueous ethanolic solution in the mole ratio 2 : 1 in presence of sodium acetate yielded the trinuclear complexes. Attempts to prepare analogous trinuclear complexes of cobalt(II) and nickel(II) resulted in only dinuclear complexes. The complexes were obtained in fine crystalline state. Analysis of the IR spectra of the precursor dialdehydes and the rnacrocycles corroborate the macrocyclic structure.